FEASIBILITY STUDY OF THE EFFECTIVENESS OF INJECTION WELLS IN OVERCOMING EXCESSIVE DECREASMENT OF GROUNDWATER LEVELS IN ANCOL AND SURROUNDING AREA, NORTH JAKARTA - Arief Suryajaya, Fachrul
Jakarta is the capital city of Indonesia, where the problem of using groundwater is increasing. North Jakarta, especially in the Ancol area and its surroundings, is an area with a decreasing level of groundwater level that has entered a critical zone, so a solution is needed to overcome this problem. The injection well method is one method that can balance the excessive use of groundwater. To determine the location and capacity of injection wells, numerical simulation of groundwater flow is required. Numerical simulation of groundwater flow is carried out under actual conditions in 2012 and projections up to 20 years. The simulation begins with a conceptual model obtained from the Jakarta logbor data which is then inputted into the VISUAL MODFLOW 2010.1 software. The research area is divided into four layers, namely unconfined aquifer, aquiclude 1, confined aquifer 1, and aquiclude 2. The number of production wells in the study area is 37 with 27 production wells for dewatering and 10 production wells for domestic use. There are 7 monitoring wells with 4 screened monitoring wells on unconfined aquifers and 3 screened monitoring wells on confined aquifers. Six injection wells were obtained, with three injection wells for unconfined aquifers and three injection wells for confined aquifers. All of the injection wells succeeded in returning the groundwater level before the production wells were turned on with a maximum rate of 6 L/s for unconfined aquifers and 1.58 L/s for confined aquifers. The injection rate test simulation was also carried out for 10 years which was offset by production wells, the result is that the injection well rate can be used in the long term.